THE INFLUENCE OF LABORATORY MEDIA USE AND MOTIVATION ON LEARNING OUTCOMES - HAUTEAS, OKRAN T.; TAEK, PAULUS; WULAKADA, HAMZA H. (Postgraduate School, Universitas Nusa Cendana, 2023)
This study aims to: 1) determine the effect of the Utilization of Laboratory Media on Learning Outcomes of Grade VIII Students in Science Subjects at Batu Putih State Middle School. 2) determine the effect of motivation on the learning outcomes of Class VIII students in science subjects at Batu Putih Public Middle School. 3) determine the effect of the use of laboratory media and motivation on the learning outcomes of Class VIII students in science subjects at Batu Putih Public Middle School. This study uses a quantitative approach to the regression model because the research results are quantitative data on the Effect of the Utilization of Laboratory Media and Motivation on Learning Outcomes of Class VIII Students in Science Subjects. The results showed that the use of Laboratory Media had an effect of 65.0% and count> table (3.629 > 1.985) and value its significance < ɑ (0.000 < 0.05), it can be concluded that there is a significant influence between Laboratory Media on student learning outcomes. For the variable motivation has an effect of 65.0% with a value of count> t table (4.878 > 1.985) and value significance < ɑ (0.000 < 0.05), it can be concluded that there is a significant influence between Laboratory Media and Motivation on student learning outcomes.